إشكالية إنشاء شبابيك الصيرفة الإسلامية في البنوك الجزائرية: بين الوضعية البنكية والمعيارية الشرعية: The problem of establishing Islamic banking windows in Algerian banks: Between the banking position and the Islamic norm - دحاك عبد النور (Journal of North African Economies, 2025)
This research aims to identify the reality of “ Islamic banking windows” in Algerian banks affiliated with interest-based banks, the reasons for their establishment and the nature of their work within the framework of the provisions of Regulation No. 02-20. It also aims to clarify the position of those interested in Islamic economic affairs from the "Islamic banking windows" and the ruling on dealing with them. Several approaches have been followed, namely: the deductive approach with its descriptive and analytical tools to collect the research material; We also tried to use the comparative approach in more than one place. The methodology of qualitative studies was used through the application of the content analysis technique, and the research concluded a set of results, the most important of which are the provisions of System No. The Islamic and the traditional in one institution leads to a shake of confidence in Islamic products due to the subordination of the “Islamic banking windows” to the conventional bank, and the jurisprudential rule says “ the follower is dependent” .